2019
DOI: 10.1016/j.celrep.2019.04.095
|View full text |Cite
|
Sign up to set email alerts
|

Mitohormesis Primes Tumor Invasion and Metastasis

Abstract: Highlights d Evidence of endogenous mitohormesis in breast cancer cell lines and primary tumors d Mitohormetic priming of tumor cells leads to increased basal activation of the UPR mt d Mitohormesis and UPR mt activation makes cancer cells more invasive and metastatic d UPR mt enriched breast cancer patients have worse clinical outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 98 publications
5
70
1
Order By: Relevance
“…Concurrent with our findings, SIRT3 has been implicated in anoikis resistance of oral squamous cell carcinoma cells [34], and for the maintenance of mitochondrial ROS scavenging in GBM stem cells [24]. In addition, the SIRT3/FOXO3a/SOD2 axis is upregulated as part of the mtUPR and necessary for breast cancer metastasis [25, 35]. Moreover, we and others have demonstrated that SOD2 is required by metastatic cells as an adaptation to oxidative stress, for the maintenance of mitochondrial fidelity, and as a regulator of mitochondria redox signaling [20, 3638].…”
Section: Discussionsupporting
confidence: 73%
“…Concurrent with our findings, SIRT3 has been implicated in anoikis resistance of oral squamous cell carcinoma cells [34], and for the maintenance of mitochondrial ROS scavenging in GBM stem cells [24]. In addition, the SIRT3/FOXO3a/SOD2 axis is upregulated as part of the mtUPR and necessary for breast cancer metastasis [25, 35]. Moreover, we and others have demonstrated that SOD2 is required by metastatic cells as an adaptation to oxidative stress, for the maintenance of mitochondrial fidelity, and as a regulator of mitochondria redox signaling [20, 3638].…”
Section: Discussionsupporting
confidence: 73%
“…This response shares similarities with the UPR mt , a homeostatic stress signaling response induced upon accumulation of misfolded proteins in the mitochondrial matrix (Shpilka and Haynes, 2017). Interestingly, is has been shown that the UPR mt is induced as an adaptive response in cells experiencing the Warburg effect (Kenny et al, 2019), suggesting that the previously reported effector-induced shift in mitochondrial metabolism (Escoll et al, 2017) might cause the induction of a UPR mt -like stress response in infected cells. However, it is also possible that the translocation of bacterial effectors into host cell mitochondria (Degtyar et al, 2009;Dolezal et al, 2012) might activate this stress response.…”
Section: Lp Induces a Mitochondrial Stress Responsementioning
confidence: 60%
“…Interestingly, the SIRT3 axis of UPR mt was shown to induce the antioxidant proteins superoxide dismutase 2 (SOD2) and catalase, and the subsequent elimination of irreversibly damaged mitochondria through mitophagy [ 47 ]. The SIRT3 arm molecular signature of the UPR mt was recently shown to contribute to breast cancer invasiveness and may be an essential mechanism for cancer cells to adapt to proteotoxic and mitochondrial stress, a process called mitohormesis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%